2015
DOI: 10.5999/aps.2015.42.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Full-Thickness Skin Grafting with De-Epithelization of the Wound Margin for Finger Defects with Bone or Tendon Exposure

Abstract: BackgroundFull-thickness skin grafts (FTSGs) are generally considered unreliable for coverage of full-thickness finger defects with bone or tendon exposure, and there are few clinical reports of its use in this context. However, animal studies have shown that an FTSG can survive over an avascular area ranging up to 12 mm in diameter. In our experience, the width of the exposed bones or tendons in full-thickness finger defects is <7 mm. Therefore, we covered the bone- or tendon-exposed defects of 16 fingers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…18,19 A full-thickness skin graft (FTSG) was applied with caution over exposed bone and tendon in the mid twentieth century, but contemporary investigators have shown that a FTSG can be reliably used in the context of exposed bone or tendon. 20 We use skin grafts judiciously for pulp reconstruction, and we note imperceptible differences between glabrous and nonglabrous graft in the long term, because the graft remodels according to stress to which it is exposed (Fig. 5).…”
Section: Skin Graftsmentioning
confidence: 99%
“…18,19 A full-thickness skin graft (FTSG) was applied with caution over exposed bone and tendon in the mid twentieth century, but contemporary investigators have shown that a FTSG can be reliably used in the context of exposed bone or tendon. 20 We use skin grafts judiciously for pulp reconstruction, and we note imperceptible differences between glabrous and nonglabrous graft in the long term, because the graft remodels according to stress to which it is exposed (Fig. 5).…”
Section: Skin Graftsmentioning
confidence: 99%
“…This is the depth that was set on the software but the specific depths of the channels were not measured after manufacturing for validation. These depths are sufficient for treating the entire thickness for many tissue‐engineered grafts (eg, full‐thickness skin grafts would be less than 7 mm thick ). The average channel width for all hydrogel types combined was 27.8 ± 5.1 and 45.6 ± 7.7 μm for 1.7 and 3.5 μJ, respectively (for all conditions combined with n = 6 or 7 spots/energy level).…”
Section: Resultsmentioning
confidence: 99%
“…Yoon et al (15) used this for reconstructing oral and/or oropharyngeal defects after surgically removing the tumor. Additionally, Jun Hee Lee et al (16) treated finger defects with exposed tendon or bone by using de-epithelialized cutaneous graft of the wound edges. Balat et al (17) obtained satisfactory result after using de-epithelialized rhomboid flap in the treatment of vulvar cancer.…”
Section: Discussionmentioning
confidence: 99%